Improved immune response of common carp (Cyprinus carpio) by administration of mahang sirap (Macaranga involucrate) Leaf Extract - Edi Ilimu; Saparuddin Saparuddin (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
This study aims to test the effectiveness of Macaranga involucrata leaf extract as an immune response in carp to increase the number of leukocytes and phagocytic activity. M. involucrata extract was injected intramuscularly into carp. The method used is Completely Randomized Design (CRD). This study was conducted with five treatments, each of which was repeated three times. The treatments were P1 = 1% (v/v), P2 = 4% (v/v), P3 = 8% (v/v), P4 = 12% (v/v) and P5 (negative control). The results showed that M. involucrata extract could respond to an increase in the number of leukocytes and an increase in phagocytic activity. Responses to an increase in the number of leukocytes (12.27 x 108 cells/mL) and phagocytic activity (45.41%) were found in P4 treatment. Based on this study it was concluded that M. involucrata extract showed an increase in the immune response of carp.